2009
DOI: 10.1111/j.1476-5381.2009.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential actions of ethanol and trichloroethanol at sites in the M3 and M4 domains of the NMDA receptor GluN2A (NR2A) subunit

Abstract: Evidence obtained to date is consistent with a role of GluN2A(Ala825) as a modulatory site for ethanol and trichloroethanol sensitivity, but not as a binding site. Trichloroethanol appears to inhibit the NMDA receptor in a manner similar, but not identical to, that of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
(76 reference statements)
1
16
1
Order By: Relevance
“…determined from propagated errors. Values for ethanol log IC 50 in GluN2A tryptophan mutants at Phe-637, Ala-825, and Met-823 are those reported previously (30,31,39).…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…determined from propagated errors. Values for ethanol log IC 50 in GluN2A tryptophan mutants at Phe-637, Ala-825, and Met-823 are those reported previously (30,31,39).…”
Section: Methodssupporting
confidence: 82%
“…Electrophysiological Recording-Whole-cell patch clamp recording was performed at room temperature using an Axopatch 1D or Axopatch 200B (Axon Instruments Inc., Foster City, CA) amplifier essentially as described previously (39). Briefly, patch-pipettes had open tip resistances of 2-8 megaohms after heat polishing; series resistances of 4 -15 megaohms were compensated by 80%.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the present study also did not show any relation between ethanol sensitivity and the hydrophilicity of the substituent at GluN2B(Phe637). Although such a relation was observed among mutants at GluN2A(Met823), indicating a possible role for hydrophobic binding (Ren et al , 2003b), similar relations were not observed for other positions (Ren et al , 2007; Salous et al , 2009). The lack of a clear role for molecular volume and hydrophobicity in the present study was particularly apparent when comparing the leucine and isoleucine mutants: there was a striking difference in ethanol sensitivity between the two mutants, even though they have identical physicochemical characteristics.…”
Section: Discussionmentioning
confidence: 76%
“…We and others have used alanine- and tryptophan-scanning to identify alcohol-sensitive positions in the GluN1 and GluN2A subunits (Ren et al , 2003b, 2007, 2012; Ronald et al , 2001; Salous et al , 2009; Smothers and Woodward, 2006). Previous studies in this laboratory identified several ethanol-sensitive positions in both the M3 and M4 domains of the GluN2A subunit: Phe636, Phe637, Met823, and Ala825 (Honse et al , 2004; Ren et al , 2003b, 2007, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol inhibition of the NMDA receptor is not determined by a single position in the membrane-associated domains, but rather the sites of ethanol action on the NMDA receptor appear to be composed of several interacting positions located in the M domains (Ren et al, 2012), each of which possess unique characteristics (Ronald et al, 2001;Ren et al, 2003bRen et al, , 2007Smothers and Woodward, 2006). For previously identified ethanol-sensitive positions in GluN2A, ethanol sensitivity was dependent on the molecular volume and hydrophilicity of the substituent at M823 (Ren et al, 2003b), was inversely dependent upon the molecular volume of the substituent at F637 (Ren et al, 2007), but was not correlated with any physicochemical measure of the substituent at A825 (Salous et al, 2009). In the GluN1 subunit, ethanol sensitivity was correlated with the molecular volume of the side chain at F639 (Smothers and Woodward, 2006), the NMDA Receptor M3 Domain Alcohol Sensitivity and Gating cognate position to GluN2A(F637).…”
Section: Discussionmentioning
confidence: 99%